Visual narratives of the Anglo-Zulu war: cattle horns engraved by an unknown African artist - Davison, P. (Southern African Humanities, 2016)
This paper adds to the published record of nineteenth-century engraved horns depicting scenes of the Anglo-Zulu war, as seen by an unknown African artist. Two pairs of engraved horns in the early collections of the KwaZulu-Natal Museum, described by Tim Maggs in 1990, form the foundation for the present account of horns that have subsequently been located in museums and private collections in South Africa, England and America. Two individual engraved horns, purchased by Iziko Museums of South Africa in 2003 and 2005, are given particular attention. The aim is not only to describe these horns in relation to other known examples but to provide more information about their historical context, as well as an interpretive reading of these and the other horns that are believed to have been engraved by the same hand. Despite research to discover the name of the artist, he remains anonymous. None the less, the engraved scenes on these horns provide rare insight into African perceptions of military encounters and other aspects of late nineteenth-century colonial life in Natal.